2020
DOI: 10.1590/2175-3369.012.e20190247
|View full text |Cite
|
Sign up to set email alerts
|

Relação entre conforto térmico urbano e Zonas Climáticas Locais

Abstract: Resumo O ambiente urbano pode impactar nas condições de conforto térmico de acordo com a sua configuração, afetando o uso do espaço e a qualidade de vida da população. Assim, é importante conhecer o nível de conforto dos espaços urbanos e as consequências para a população para propor soluções construtivas adequadas. Este artigo objetiva analisar a influência da forma urbana e da cobertura do solo no conforto térmico dos usuários de espaços públicos ao ar livre. Para isso, foram caracterizadas quatro frações da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
(20 reference statements)
0
1
0
1
Order By: Relevance
“…According to the American Society of Heating, Refrigerating, and Air-Conditioning Engineers (ASHRAE) thermal comfort refers to "that condition of mind that expresses satisfaction with the thermal environment and is assessed by subjective evaluation" [11]. Commonly used thermal indices include predicted mean vote (PMV) [12], physiological equivalent temperature (PET) [13], and universal thermal climate index (UTCI) [14]. Shakoor reviewed the relationship between summertime temperature and mortality and showed that the risk of mortality increases by 1 to 3% with a 1 • C increase in mean temperature [15].…”
Section: Introductionmentioning
confidence: 99%
“…According to the American Society of Heating, Refrigerating, and Air-Conditioning Engineers (ASHRAE) thermal comfort refers to "that condition of mind that expresses satisfaction with the thermal environment and is assessed by subjective evaluation" [11]. Commonly used thermal indices include predicted mean vote (PMV) [12], physiological equivalent temperature (PET) [13], and universal thermal climate index (UTCI) [14]. Shakoor reviewed the relationship between summertime temperature and mortality and showed that the risk of mortality increases by 1 to 3% with a 1 • C increase in mean temperature [15].…”
Section: Introductionmentioning
confidence: 99%
“…As zonas rurais, ao passo em que são devastadas, têm se transformado em "cidades dormitórios", com urbanização deficiente, desmatamento, atividades agropecuárias prejudicadas pela especulação imobiliária, pela invasão de novos moradores, pela poluição, degradação do solo e sua vegetação, pela redução da produção e economia do campo, exclusão social, deficit de habitação, ofensa ao legítimo direito à moradia digna, ofensa ao meio ambiente ecologicamente equilibrado e ofensa à função social da cidade (OJIMA, 2007; RAGAZZO; LIMA, 2013;LONDE;MENDES, 2014;SANTOS et al, 2017;FERNANDES;MASIERO, 2020;MORAIS;SILVA NETO, 2020;SEIXAS;BAPTISTA;DIAS, 2020).…”
Section: Introductionunclassified